INFLUENCE OF THE HUMILID FEED ADDITIVE ON THE REPRODUCTIVE ABILITY OF SOWS - Shostya, M.; Pavlova, I.; Usenko, O.; Moroz, O.; Slynko, V.; Krasnoshchok О.; Litvinov, P. (Scientific Progress & Innovations, 2021)
For modern industrial production in pig breeding, it is important to have a rapid rate of the reproduction of livestock and the high productivity of sows, without losses and with minimal reduction in weight gain under the stress of the industrial process. The aim of the study was to determine the effect of humic substances on prooxidant-antioxidant homeostasis in blood of sows and piglets under the action of stress factors. In the experiment, pregnant sows of the Large White breed were used, 5 of which were from the control group and 5 from the experimental group, which received the biologically active feed additive Humilid during the experiment. It has been determined that the state of prooxidant-antioxidant homeostasis in blood of pregnant sows in the future after farrowing and weaning the piglets, is accompanied by important physiological processes that correspond to each of the successive subperiods. Biochemical indexes of blood are a mirror image of the physiological status of animals and characterize the functional state of sows in each subperiod. The content of SOD in blood of sows at the beginning of the experiment (104 days of gestation) and 5 days after farrowing decreased by 19.6 % (p<0,01). At that time, at the time of weaning, there was a probable increase in the rate by 21.5 % (p<0.01) compared to the initial period. CT activity from the beginning of the experiment and on the 5th day of farrowing decreased by 38.4 % (p<0.001), the decrease in concentration at the time of weaning was 8.1 %. The content of diene conjugates in blood on the 5th day after farrowing fluctuated slightly in the direction of decrease compared to the previous period by 1.8% and at the time of weaning was 4.8 %. The largest number of TBA-active complexes in blood of sows were in the gestation period of 15.6 μmol/l. Additional feeding to sows of the feed additive "Humilid" during gestation affected the activation of the course of antioxidant defence, as antioxidants decreased, and the decay products tended to increase slightly. Feeding the feed additive "Humilid" to piglets of the experimental group contributed to the active generation of SOD in blood on the 5th day after birth, and was by 20.5 % more than in animals of the control group. At the time of weaning, this index was by 25 % (p<0.001) higher compared to control. The positive effect of Humilid on the reproductive capacity of sows of the experimental group was determined, the increase of high fertility by 9.4 % (p<0.01) was revealed in accordance with the control group of animals.